Dilating time for found spaces - Marcondes Machado, Marina (Mimesis Journal, 2013)
This presentation chronicles the preparation, execution, recording, and post-event analysis of installations that undergraduate students of the course “Analysis of Practice: Theatre Workshop II” (Bachelor in Theater, Federal University of Minas Gerais, Brazil) performed in public spaces in Belo Horizonte, where the students urged passersby to get involved in the happenings, the aim of which was to reveal latent theatricalities in spaces found initially by the trainees, and then by site users. We named these installations “dramaturgies of space”, attuned to trends of contemporary theater research that melds performing arts and visual arts. To be fully comprehended and enjoyed, these installations require a dilated sense of time, with the absence of time-keeping and of how-to sets of instructions. It is an experiment in the radical emancipation of the spectator, as proposed by Rancière. Our objectives included: enabling college-level theater majors to engender their poiesis through understanding the wealth contained in the dramaturgy of space, and to return their creations to their viewers; developing in students their ability to observe the use made by “the other” of the space that they (the students) created, while refraining from manipulating the contemplative processes of the viewers, the action processes of the players, or the understanding processes of “those who do not understand”; providing users of a city park (with special emphasis on children’s perspectives) an experience of the theatric potentialities of space free from the habits and demands of school, as well the standardized classroom clock.